2018
DOI: 10.1186/s13045-017-0550-8
|View full text |Cite
|
Sign up to set email alerts
|

A phase I study of selinexor in combination with high-dose cytarabine and mitoxantrone for remission induction in patients with acute myeloid leukemia

Abstract: BackgroundNovel therapies for patients with acute myeloid leukemia (AML) are imperative, particularly for those with high-risk features. Selinexor, an exportin 1 (XPO1/CRM1) inhibitor, has demonstrated anti-leukemia activity as a single agent, as well as in combination with anthracyclines and/or DNA-damaging agents.MethodsWe report the findings of a phase I dose escalation trial with cohort expansion in 20 patients with newly diagnosed or relapsed/refractory AML that combined selinexor with age-adjusted high-d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(37 citation statements)
references
References 35 publications
1
36
0
Order By: Relevance
“…The authors concluded that Selinexor is a safe therapy in AML patients, and established the RP2D at 35 mg/m 2 (60 mg flat dose) given twice weekly. Another phase I doseescalation trial in AML evaluated the combination of Selinexor with high-dose cytarabine and mitoxantrone in 20 patients [198] . Selinexor doses of 60 mg or 80 mg were administered.…”
Section: In Vitromentioning
confidence: 99%
“…The authors concluded that Selinexor is a safe therapy in AML patients, and established the RP2D at 35 mg/m 2 (60 mg flat dose) given twice weekly. Another phase I doseescalation trial in AML evaluated the combination of Selinexor with high-dose cytarabine and mitoxantrone in 20 patients [198] . Selinexor doses of 60 mg or 80 mg were administered.…”
Section: In Vitromentioning
confidence: 99%
“…More than 1000 patients have been exposed to selinexor in these trials combined. The published results of several of these trials have shown evaluable response in patients and support the safety and efficacy of selinexor for the treatment of cancer [ 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 ].…”
Section: Chemical Inhibition Of Nuclear Exporter Function In Cancementioning
confidence: 82%
“…Formalin-fixed paraffin-embedded sections (5 μm) were cut from untreated BALB/cJ mouse RENCA tumors. Immunohistochemistry was performed as previously described (31) using the following antibodies, Ki67 (Cell Marque, 275R-18), PD-L1 (Cell Signaling Technology, 13684) and PD-L2 (Cell Signaling Technology, 82723).…”
Section: Immunohistochemistrymentioning
confidence: 99%